Vortioxetine ameliorates motor and cognitive impairments in the rotenone-induced Parkinson's disease via targeting TLR-2 mediated neuroinflammation. (1st May 2022) - Nemutlu Samur, Dilara; Akçay, Güven; Yıldırım, Sendegül; Özkan, Ayşe; Çeker, Tuğçe; Derin, Narin; Tanrıöver, Gamze; Aslan, Mutay; Ağar, Aysel; Özbey, Gül
Abstract: Parkinson's disease (PD) is characterized by motor and non-motor symptoms associated with dopaminergic and non-dopaminergic injury. Vortioxetine is a multimodal serotonergic antidepressant with potential procognitive effects. This study aimed to explore the effects of vortioxetine on motor functions, spatial learning and memory, and depression-like behavior in the rotenone-induced rat model of PD. Male Sprague-Dawley rats were daily administered with the rotenone (2 mg kg −1, s.c.) and/or vortioxetine (10 mg kg −1, s.c.) for 28 days. Motor functions (rotarod, catalepsy, open-field), depression-like behaviors (sucrose preference test), anxiety (elevated plus maze), and spatial learning and memory abilities (novel object recognition and Morris water maze) were evaluated in behavioral tests. Then immunohistochemical, neurochemical, and biochemical analysis on specific brain areas were performed. Vortioxetine treatment markedly reduced rotenone-induced neurodegeneration, improved motor and cognitive dysfunction, decreased depression-like behaviors without affecting anxiety-like parameters. Vortioxetine also restored the impaired inflammatory response and affected neurotransmitter levels in brain tissues. Interestingly, vortioxetine was thought to trigger a sort of dysfunction in basal ganglia as evidenced by increased Toll-like receptor-2 (TLR-2) and decreased TH immunoreactivity only in substantia nigra tissue of PD rats compared to the control group. The present study indicates that vortioxetine has beneficial effects on motor dysfunction as well as cognitive impairment associated with neurodegeneration in the rotenone-induced PD model. Possible mechanisms underlying these beneficial effects cover TLR-2 inhibition and neurochemical restoration of vortioxetine. Graphical abstract: Possible mechanisms of action of vortioxetine in the rotenone-induced rat model of Parkinson's disease. (1) Vortioxetine improves motor and cognitive deficits as well as depression, (2) vortioxetine decreases α-synuclein phosphorylation, (3) vortioxetine inhibits TLR-2 activation, (4) vortioxetine changes pro-inflammatory cytokine levels and (5) neurotransmitter levels in Parkinsonian rats. Image 1 Highlights: Non-dopaminergic injury leads to non-motor symptoms in PD. Vortioxetine attenuates rotenone-induced motor and cognitive impairments. Vortioxetine may cause a mild dysfunction in SNpc tissue. Vortioxetine alters neurotransmitter and cytokine levels in PD rat brains. Targeting TLR-2 signaling may help to fight motor and non-motor symptoms in PD.